Retention systems in extraoral prosthesis - Anjali Gopinath Pai (Wolters Kluwer Medknow Publications, 2024)
Prosthodontist plays a very important part in the reconstruction of extraoral defects. Prosthetic rehabilitation of huge maxillofacial defects will be a crucial process for a prosthodontist. The rehabilitation depends on multiple factors such as size, site, etiology, extension of the defect, age of the patient, patient's comfort, patient's satisfaction, and treatment cost. The experience, skill, and knowledge of both a surgeon and a prosthodontist help to decide the foremost mode of retention possible for the rehabilitation of maxillofacial prosthesis. Achieving adequate retention for maxillofacial prosthesis is a great challenge. Various conventional methods are there for retention of maxillofacial prosthesis but treatment modalities became advanced with the rise of osseointegrated implants. Periodic evaluation of prosthesis must be carried to determine the retention, stability, function as well as esthetics of the extraoral prosthesis which enhances the well-being and satisfaction of patients. In this review, we collected the articles from PubMed as well as Scopus-indexed journals and limited to research articles published from 1976 to 2020.